Legal Protection Of OVO E-Wallet Users As An Electronic Means Of Payment - Lahtifa, Fitri Dorrotul; Ambarini, Nur Sulistyo B.; Fitriah, Nurhani (UI Scholars Hub, 2023)
The development of an era that is increasingly sophisticated with the emergence of various technologies, one of which is the OVO E-wallet, which can make it easier for people to make payments, the public can also easily access using the OVO E-wallet, anytime and anywhere. OVO is the most widely used E-wallet for online and offline transactions with the largest number of active users, 31%. The total number of E-wallet users in the country has been recorded at 63.6 million. In using the OVO application, problems that occur that harm OVO users include doing top up OVO but the results of the top up do not come in but the balance in the account has been deducted and also when making transactions via OVO to another account where the balance in OVO is already deducted and the delivery notification was successful but the balance did not appear in the destination account. The purpose of this study is to analyze and find out about the legal protection of OVO E-wallet users as an electronic payment tool and to describe the responsibility of the OVO E-wallet for losses experienced by consumers. This research is a type of normative legal research with a statutory and legal approach. The case approach is by reviewing all legislation related to legal issues and building legal arguments in cases. Based on the results of the study, it can be understood that the agreement given by the OVO E-Wallet to the user is a standard agreement. Legal protection for OVO E-Wallet users is regulated in the Consumer Protection Act, the Basic Law, OJK and the ITE Law. The form of OVO E-wallet’s responsibility to OVO users is to return money to users who have suffered losses.